Pengaruh E-Service Quality terhadap Repurchase Intention melalui E-Satsifaction pada Pengguna Aplikasi E-Grocery - Rizqi Adi Wiatna; Sanaji Sanaji (Inspirasi Nusantara, 2022)
This study aims to analyze the effect of e-service quality on repurchase intention through e-satisfaction in users of the E-Grocery application. This research uses a quantitative research approach. Data analysis used the SEM-PLS approach supported by Smart-PLS 3.0 software. The online questionnaire was distributed through several social media to get 200 respondents who met the requirements. Respondents in this study are users of the E-Grocery application in Indonesia. The results reveal that there is a significant positive effect between e-service quality and repurchase intention, e-service quality and e-satisfaction, e-satisfaction and repurchase intention, and e-satisfaction positively mediates the effect of e-service quality on repurchase intention. This study focuses on the effect of e-service quality and e-satisfaction on repurchase intention. In addition, this research is focused on E-Grocery application users. This kind of research can be a consideration tool for E-Grocery companies and the like in attracting new users and retaining old ones. Therefore, it is necessary to include this topic of discussion as a reference in further research or practice for companies.